VD_FINDINFO Décision / 2012 / 701 vom 10. August 2012 - VD Tribunal cantonal (2012)
DÉTENTION PRÉVENTIVE, RISQUE DE FUITE, PROLONGATION, MISE EN LIBERTÉ PROVISOIRE | 221 CPP (CH), 222 CPP (CH), 227 CPP (CH), 228 CPP (CH), 393 al. 1 let. c CPP (CH)